Experimental Study on the Forward and Inverse Solution of 5R Planar Parallel Mechanism with Large Workspace - Wu Xiao; Qin Huibin; Shen Xuyang; Hou Zhili; Niu Jinrong (Jixie chuandong)
Aiming at the shortage that the workspace of planar parallel mechanism with two degrees of freedom is small,a 5 R mechanism of variable drive layout of large workspace is presented. On the basis of kinematics analysis,3 D kinematics simulation analysis model of parallel mechanism is built by using the SolidWorks. The motion trajectory and workspace of the parallel mechanism are solved by changing the motion parameters of cranks in the environment of Motion analysis. The forward solution analysis is completed. In addition,the kinematics experimental platform of parallel mechanism is built. The required trajectory can be drawn in Solid Works. Two servo motors’ speeds of any time can be obtained by inverse solution of Solid Works. Combined with the motion control functions,the running program of PC is written. The servo motors are controlled by PCI-DMC-F01 motion control card. Therefore,the end effector can move along the desired trajectory. The experimental trajectory and workspace are in accord with the results of the forward and inverse solutions. The experimental results show that the forward and inverse solution of 5 R mechanism is correct and feasible. In addition,on the basis of it,the application example of parallel mechanism with large workspace is provided. This research has reference value for the engineering application of 5 R parallel mechanism.